Investigando a participação do cônjuge nos cuidados ao paciente com dor lombar crônica - Maeda, Fernando Lourenço (2008)
This study had as general goal investigate the perception of partner s support and the impact of the pain in the relationship as a couple of patients suffering of chronic lower back pain, of both gender, in ambulatory treatment in a big public hospital of São Paulo city. The study was made with 50 patients, where 25 were men and 25 were women, aged 35 to 65 years. The main used instruments were: social-demographic questionnaire, visual analogical scale of pain intensity, medical Outcomes study 36- item short form-health survey and semi directed interviews. The results demonstrated that all the participants of the study had the quality of their lives harmed, and that women showed intensity pain levels considered severe, whereas men obtained intensity pain levels considered moderate. 70% percent of the sample mentioned a negative impact on their sexual relations, due to their functional limitation and intensity of the pain, while the rest mentioned a marital adjustment when facing the symptoms of the pain. 86% of the sample mentioned perceiving their partners as supportive, being the helpful behavior considered the main way of support. The analysis of the results showed that the participants that had received partner s support, obtained better levels in the control of Vitality and Mental Health, when compared to the ones that had had no support. The conclusion of the results indicated that the chronic lower back pain causes a negative impact in the couple s relationship and that the partners support can work as a protection factor for depressive and anxiety symptoms, being this an important aspect to be considered in the health process of individual with chronic pain and in the planning of therapeutic procedures